Laser‐assisted cataract surgery versus standard ultrasound phacoemulsification cataract surgery - Day, Alexander C (Cochrane Database Syst Rev, 2016)
BACKGROUND: Cataract is the leading cause of blindness in the world, and cataract surgery is one of the most commonly performed operations in the Western world. Preferred surgical techniques have changed dramatically over the past half century with associated improvements in outcomes and safety. Femtosecond laser platforms that can accurately and reproducibly perform key steps in cataract surgery, including corneal incisions, capsulotomy and lens fragmentation, are now available. The potential advantages of laser‐assisted surgery are broad, and include greater safety and better visual outcomes through greater precision and reproducibility. OBJECTIVES: To compare the effectiveness of laser‐assisted cataract surgery with standard ultrasound phacoemulsification cataract surgery by gathering evidence on safety from randomised controlled trials (RCTs). SEARCH METHODS: We searched CENTRAL (which contains the Cochrane Eyes and Vision Trials Register) (2016, Issue 4), Ovid MEDLINE, Ovid MEDLINE In‐Process and Other Non‐Indexed Citations, Ovid MEDLINE Daily, Ovid OLDMEDLINE (January 1946 to May 2016), EMBASE (January 1980 to May 2016), Latin American and Caribbean Health Sciences Literature Database (LILACS) (January 1982 to May 2016), the ISRCTN registry (www.isrctn.com/editAdvancedSearch), ClinicalTrials.gov (www.clinicaltrials.gov), the World Health Organization (WHO) International Clinical Trials Registry Platform (ICTRP) (www.who.int/ictrp/search/en) and the U.S. Food and Drugs Administration (FDA) website (www.fda.gov). We did not use any date or language restrictions in the electronic searches for trials. We last searched the electronic databases on 10 May 2016. SELECTION CRITERIA: We included randomised controlled trials where laser‐assisted cataract surgery was compared to standard ultrasound phacoemulsification cataract surgery. We graded the certainty of the evidence using GRADE. DATA COLLECTION AND ANALYSIS: Two review authors independently screened the search results, assessed risk of bias and extracted data using the standard methodological procedures expected by Cochrane. The primary outcome for this review was intraoperative complications in the operated eye, namely anterior capsule and posterior capsule tears. The secondary outcomes were visual acuity (corrected distance visual acuity (CDVA) and uncorrected distance visual acuity (UDVA)), refractive outcomes, quality of vision (as measured by any validated visual function score), postoperative complications and cost‐effectiveness. MAIN RESULTS: We included 16 RCTs conducted in Germary, Hungary, Italy, India, China and Brazil that enrolled a total of 1638 eyes of 1245 adult participants. Overall, the studies were at unclear or high risk of bias. In 11 of the studies the authors reported financial links with the manufacturer of the laser platform evaluated in their studies. Five of the studies were within‐person (paired‐eye) studies with one eye allocated to one procedure and the other eye allocated to the other procedure. These studies were reported ignoring the paired nature of the data. The number of anterior capsule and posterior capsule tears reported in the included studies for both laser cataract surgery and manual phacoemulsification cataract surgery were low. There were four anterior capsule tears and one posterior capsule tear in 1076 eyes reported in 10 studies (2 anterior capsule tears in laser arms, 2 anterior capsule tears and 1 posterior capsule tear in standard phacoemulsification arms). We are very uncertain as to the effect of laser‐assisted surgery compared to standard phacoemulsification surgery with respect to these two outcomes. For postoperative cystoid macular oedema and elevated postoperative intraocular pressures, again the evidence was inconclusive (odds ratio (OR) 0.58, 95% confidence interval (CI) 0.20 to 1.68; 957 eyes, 9 studies, low certainty evidence; and OR 0.57, 95% CI 0.11 to 2.86; 903 eyes, 8 studies, low certainty evidence). We found little evidence of any important difference in postoperative visual acuity between laser‐assisted and standard phacoemulsification arms. There was a small advantage for laser‐assisted cataract surgery at six months in CDVA. However, the mean difference (MD) was ‐0.03 logMAR (95% CI ‐0.05 to ‐0.00; 224 eyes, 3 studies, low certainty evidence) which is equivalent to 1.5 logMAR letters and is therefore, clinically insignificant. No studies reported patient‐reported outcome measures such as visual function. There were no data reported on costs or resource use but three studies reported the time taken to do the surgery. There was little evidence of any major difference between the two procedures in this respect (MD 0.1 minutes, 95% CI ‐0.02 to 0.21; 274 eyes, low certainty evidence). AUTHORS' CONCLUSIONS: The evidence from the 16 randomised controlled trials RCTs included in this review could not determine the equivalence or superiority of laser‐assisted cataract surgery compared to standard manual phacoemulsification for our chosen outcomes due to the low to very low certainty of the evidence available from these studies. As complications occur rarely, large, adequately powered, well designed, independent RCTs comparing the safety and efficacy of laser‐assisted cataract surgery with standard phacoemulsification cataract surgery are needed. Standardised reporting of complications and visual and refractive outcomes for cataract surgery would facilitate future synthesis. Data on patient‐reported outcomes and cost‐effectiveness are needed. Paired‐eye studies should be analysed and reported appropriately.